Digital Education Research: Advantages, Disadvantages, and Video Illustrations (LEARNing Landscapes, 2022)
Although anthropological methods have been appropriated by qualitative and mixed-methods educational researchers, visual anthropology has had virtually no impact on educational research. Furthermore, video, in general, despite its widespread impact on 21st century culture, has played only a limited role in the doing of education-related studies and almost no role in reporting study results. This paper explores what would be gained and lost if researchers began using video in the doing and, especially, in the reporting of their research. The paper uses clips from four author-developed research videos to illustrate the advantages and disadvantages associated with educational researchers “going digital.”
Keywords: digital educational research; arts-based inquiry; qualitative research; video data; digital video